Asuhan Kebidanan Komprehensif Ny “S” dengan Anemia Ringan di Puskesmas Pangale Kabupaten Mamuju Tengah - Mahmud, Abbas; Nurdiana, Nurdiana; Ulandari, Ratni (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2020)
Anemia in pregnancy is a national problem because it reflects the value of the socioeconomic welfare of the community, and its influence is very large on the quality of human resources. Pregnancy anemia is called